Synthesisation of CaCl2-in-zeolite adsorbents for water based isotherms and kinetics study - Lee, Geoffery Gan He (2019)
Climate changes in recent decades have brought about more attention towards renewable energy systems and technology that releases less greenhouse gases, such as hydrochlorofluorocarbons, into the environment, and reduced energy wastages. Hence, the adsorption chiller is perceived as one of the solutions to the problem of climate change and thus giving the notion that it will eventually replace conventional vapour compression cycle chillers.